Who am I? - Christensen, Nancy; Barnes-Murphy, Rowan (New York : Scholastic, 1993)
Rhyming text provides clues about the nature of the animal who is speaking. Includes activity pages.
"Cartwheel Books."
"With flash cards."
BR
BR
Keywords: Animals -- Fiction; Literary recreations; Stories in rhyme